School Principal’s Strategy in Improving Students’ Non-Academic Achievement of State Elementary School in Jember - Hayati, Nurul; Abidin, Zainal (Fakultas Tarbiyah dan Ilmu Keguruan Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2023)
The purpose of this study was to reveal the principal's strategy in mapping and facilitating student talents and interests, funding support in increasing student non-academic achievement, and stakeholder involvement in improving student non-academic achievement. This research used a qualitative approach with a case study type. Data collection techniques consisted of interviews, observation, and documents. Data analysis used interactive analysis consisting of reduction, presentation, and verification. The results of this study indicate that school principals play an essential role in identifying and understanding students' talents, interests, and skills. Funding support is also a key factor in increasing non-academic achievements. In addition to budgets sourced from the government and regional governments, school principals actively seek additional funding sources through sponsors. This effort ensures that students can participate in non-academic training and competition activities. In addition, stakeholder involvement is also an essential element. Principals always try to gain support from school stakeholders, especially teachers, parents, and the community, to support students' non-academic achievements.